Genetic diversity of Phlebotomus (Euphlebotomus) argentipes species complex in Sri Lanka - Sharmintha, P.; Gajapathy, K.; Amarasinghe, A.A.K.P.; Surendran, S.N. (Ceylon Journal of Science, 2022)
Leishmaniasis has been recognized in Sri Lanka for many years and is becoming a serious public health threat. Sandflies, the known vector of leishmaniasis, are also found throughout the country. The presence of a species complex among the potential vector species; Phlebotomus (Euphlebotomus) argentipes sensu lato is one of the impediments to developing an effective control strategy. The current study assessed the genetic diversity of the species complex and compared the results to morphology-based taxonomy. Sandflies were collected from selected study sites in the Anuradhapura, Hambantota, Puttalam, and Jaffna districts between 2015 and 2018. They were identified morphologically using existing taxonomic keys. The PCR assay and subsequent DNA sequence analysis were performed for the cytochrome c oxidase subunit I (COI) gene. The morphological analysis revealed that the species complex contains more than two morphospecies. Nucleotide variation was observed in the COI sequences that were aligned. The uncorrected p distances within and between groups were 0.01%-0.08% and 2.1%, respectively. The COI sequence-based phylogenetic tree revealed the presence of two genetically distinct groups: one with a sensilla chaetica/ second antennal flagellomere length ratio of less than 0.4 and another with a ratio of 0.45 and greater. This result contradicts the existing taxonomic keys. A PCR-based assay is proposed to differentiate the genetic groups based on the sequence variations.
Keywords: Argentipes complex; Morphospecies; Molecular taxonomy; PCR